Marked hypereosinophilia secondary to endometrioid ovarian cancer presenting with asthma symptoms, a case report - Hasan Ahmad Hasan Albitar; Ashley M. Egan; Hassan Alkhateeb; Yahya Almodallal; Vivek N. Iyer (Respiratory Medicine Case Reports, 2020)
Background: Hypereosinophilia (HE) is defined by the presence of >1.5 × 109/L eosinophils in the peripheral blood. Paraneoplastic HE has been reported in a number of solid and hematologic malignancies including ovarian cancer. We present a case with paraneoplastic HE in the setting of underlying endometrioid ovarian carcinoma. Case presentation: An 88-year-old woman presented with cough, dyspnea and 20-pound unintentional weight loss of one month duration. Evaluation revealed peripheral hypereosinophilia (HE) with absolute eosinophil count of 15.38 × 109/L (53.8%) and an elevated exhaled nitric oxide at 172 parts per billion (normal < 39 PPB). Given the HE and unintentional weight loss, computed tomography (CT) scan was obtained and showed a pelvic mass. The patient underwent bilateral salpingo-ophorectomy with pathology consistent with endometrioid ovarian carcinoma. The patient experienced complete resolution of her cough, dyspnea, and peripheral eosinophilia following surgical resection. Conclusion: This case highlights that solid malignancy should be considered in patients with marked HE.